2014
DOI: 10.1088/0004-637x/796/2/116
|View full text |Cite
|
Sign up to set email alerts
|

SPITZER/INFRARED SPECTROGRAPH INVESTIGATION OF MIPSGAL 24 μm COMPACT BUBBLES: LOW-RESOLUTION OBSERVATIONS

Abstract: We present Spitzer/IRS low resolution observations of 11 compact circumstellar bubbles from the MIPSGAL 24 µm Galactic Plane Survey. We find that this set of MIPSGAL bubbles (MBs) is divided into two categories, and that this distinction correlates with the morphologies of the MBs in the mid-IR. The four MBs with central sources in the mid-IR exhibit dust-rich, low excitation spectra, and their 24 µm emission is accounted for by the dust continuum. The seven MBs without central sources in the mid-IR have spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…We have showed that at 24 µm a large sample of known post-AGB stars appear as very bright point sources. On the other hand, almost all the MBs classified as PN are 'disks' or 'rings' (Figure 2; Nowak et al 2014). We infer that the most probable morphology for a PPN MB would be that of a 'disk'.…”
Section: Post-agb Stars and Ppne With Spitzermentioning
confidence: 79%
“…We have showed that at 24 µm a large sample of known post-AGB stars appear as very bright point sources. On the other hand, almost all the MBs classified as PN are 'disks' or 'rings' (Figure 2; Nowak et al 2014). We infer that the most probable morphology for a PPN MB would be that of a 'disk'.…”
Section: Post-agb Stars and Ppne With Spitzermentioning
confidence: 79%
“…The categories most populated are 'ring' and 'disk' nebulae, accounting for 339 objects out of 428. 9 As previously discussed, Nowak et al (2014) found that more than 80 per cent of classified 'ring' and 'disk' bubbles are PNe, and that few other PNe are found in other categories. It is possible to estimate that the entire bubbles sample should contain about 300 PNe.…”
Section: Completeness Of the Bubbles Catalogue With Respect To Planetmentioning
confidence: 80%
“…This can be ascribed to the homogeneity of the original 24-µm sample, consisting of objects with a similar angular extension and shape. We recall that Nowak et al (2014) pointed out that almost all bubbles classified as PNe show a disk or ring morphology. PNe with very different 24-µm shape were excluded a priori by Mizuno et al (2010).…”
Section: Physical Propertiesmentioning
confidence: 86%
See 1 more Smart Citation
“…MN48 is prominent at 24 µm, in all IRAC and WISE 2 http://simbad.harvard.edu/simbad/ 3 Spitzer spectroscopy of circumstellar nebulae around evolved massive stars showed that their emission is dominated by the dust continuum emission (Flagey et al 2011;Nowak et al 2014). Detection of the nebula around MN48 at longer wavelengths (e.g.…”
Section: Mn48 and Its Mid-infrared Nebulamentioning
confidence: 99%